Natural resources management in African agriculture : understanding and improving current practices (CABI Publishing, in association with the International Centre for Research in Agroforestry, 2002)
This book synthesizes existing information on the adoption of natural resource management investments and strategies (such as soil fertility improvements or erosion control) for agriculture in sub-Saharan Africa. It also critically examines current analytical methods and generates research and policy recommendations. Topics covered include: farmers' objectives and learning processes; willingness and capacity to make long-term investments; economic incentives and the importance of the resource base; and the agroecological, institutional and policy contexts. The book has 22 chapters and a subject index.